Beginning iOS 6 Games Development - Jordan, Lucas (Apress : Imprint: Apress, 2012)
Game apps on iPhone and now The New iPad remain one of the most popular type of apps in the Apple iTunes App Store. Does Angry Birds ring a bell?  Now, you can learn to build game apps for the iPhone 5 and The New iPad using the new iOS 6 SDK.    Beginning iOS 6 Games Development provides a clear path for you to learn and create iPhone and iPad game apps using the iOS 6 SDK platform. You'll learn how to use the core classes to create rich and dynamic games apps, including graphics, animations, and sound. The latest version of Xcode 4.5 will be used in parts of the book to guide you along the way of building your iPhone or iPad game apps. Other topics include iOS 6 game apps development with the newest iOS Game Center update, persisting user data, and designing a compelling user experience. After reading this book, you'll come away with the skills and techniques for building a game app, top to bottom, that could perhaps even be sold on the Apple iTunes App Store. *** NOTE: This book is an update of Beginning iOS 5 Games Development (ISBN-13: 978-1430237105) and Beginning iPhone Games Development (ISBN-10: 1430225998).